Optimizing polymerase chain reaction testing for the diagnosis of pertussis: current perspectives - Arbefeville S; Ferrieri P (Dove Medical Press, 2015)
Sophie Arbefeville, Patricia Ferrieri Department of Laboratory Medicine and Pathology, University of Minnesota Medical School, Minneapolis, MN, USA Abstract: Nucleic acid testing has revolutionized the diagnosis of pertussis in the clinical microbiology laboratory and has become the main avenue of testing for pertussis infection. Real-time polymerase chain reaction (RT-PCR) is an important tool for timely diagnosis of pertussis and is more sensitive than culture. The most commonly amplified targets are the insertion-sequence (IS) genes, which are found in multiple copies in the genome of Bordetella species. Some strains of Bordetella pertussis have more than 200 copies of IS481 in their genome. This high number of repeats allows RT-PCR assays to be very sensitive and makes nucleic acid testing two to three times more sensitive than culture. Despite these advantages, RT-PCR can give inaccurate results due to contamination or lack of specificity. Contamination can easily happen during specimen collection, DNA extraction, or nucleic acid amplification steps. To avoid contamination, laboratories need to have quality controls and good workflows in place. The poor specificity of the nucleic acid assays amplifying the IS genes is because they are found in various Bordetella species and, thus, not unique to a specific species. Bordetella holmesii, a more recently described Bordetella species found to be responsible for respiratory symptoms similar to pertussis in adolescents and adults, can be misidentified as B. pertussis in RT-PCR assays that amplify only the IS481 target. Use of multiple targets may improve specificity of RT-PCR assays for pertussis. In the past few years, the US Food and Drug Administration has cleared three commercial assays for the detection of B. pertussis in respiratory specimens. Several commercial assays and analyte-specific reagents, which are not US Food and Drug Administration cleared, are available for the detection of one or more Bordetella species by nucleic acid testing. Because of the diversity of nucleic acid amplification assays used, pertussis testing is not standardized across clinical laboratories. Keywords: nucleic acid testing, real-time PCR, Bordetella pertussis, Bordetella species